2017
DOI: 10.5114/aoms.2016.58925
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of platinum nanoparticle properties against U87 glioblastoma multiforme

Abstract: IntroductionGliomas are the most aggressive and common primary tumors of the central nervous system (CNS). Many side effects of drugs containing platinum and their poor penetration of the CNS are major drawbacks in glioma therapy. The aim of the study was to investigate and compare the toxicity of platinum nanoparticles and cisplatin and their anticancer properties in examination with a U87 glioma cell line and tumor.Material and methodsNanoparticles of platinum (NP-Pt) and cisplatin were incubated with U87 gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…AZ31 alloy extract (40%) showed significantly increased expression of NF-kB at a regular time interval. A similar result was observed in the TNF-α concentration; AZ31 alloy extract (40%) demonstrated increased expression [52][53][54]58]. Another apoptosis parameter, caspase-3, is considered as a significant marker of inflammation and plays an important role in the apoptosis pathway [57].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…AZ31 alloy extract (40%) showed significantly increased expression of NF-kB at a regular time interval. A similar result was observed in the TNF-α concentration; AZ31 alloy extract (40%) demonstrated increased expression [52][53][54]58]. Another apoptosis parameter, caspase-3, is considered as a significant marker of inflammation and plays an important role in the apoptosis pathway [57].…”
Section: Discussionsupporting
confidence: 73%
“…Several apoptosis mediators such as caspase-3, TNF-α and NF-kB play an important role in the apoptosis mechanism [49,50]. The apoptosis mediators are activated via transactivating gene expression of anti-apoptosis [51][52][53][54]. Several researchers suggest that the NF-kB pathway is a crucial factor in the cell reaction to apoptotic stimuli [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PtNPs penetrate cells via diffusion or endocytosis and then form intracellular aggregates [5,[41][42][43]. Platinum NPs inhibit HeLa cell viability and proliferation by activating p53 [41] and inhibiting U87, U118, and U251 glioblastoma tumor cell proliferation [41,44,45]. Cytotoxicity is dependent on PtNP size in Raw 264.7 cells incubated with various concentrations of PtNPs [46].…”
Section: Effects Of Ptnps On Cell Viability and Proliferation Of Thp-mentioning
confidence: 99%
“…The PtNPs exhibited poor cellular apoptosis possibly due to the fact that PtNPs have anti-oxidative stress properties similar to those of cellular antioxidant enzymes (Adeyemi et al, 2018a). Nevertheless, studies have demonstrated in vitro apoptotic tendency of PtNPs in cancer cells, human fibroblast as well as in bacteria cells (Bendale et al, 2017;Kutwin et al, 2017; bacterial cells and HFF cells (Nejdl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%